Environment Design sebagai Mediator Interaksi Pemain pada Game Point-and-Click: Studi Kasus Return to Monkey Island - Aliyyah Nurfitri; Aditya Januarsa (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2026)
Point-and-click game genre had experienced a decline in popularity due to its mismatch with the preferences of modern players and the potential cognitive burden caused by environmental design and puzzle mechanics that can lead to frustration. This issue warrants further investigation through a case study of “Return to Monkey Island” to understand how the composition of in-game objects influences player experience and their overall perception of the point-and-click genre. Using a controlled playthrough method, environmental objects in Return to Monkey Island were classified into three categories: interactive, animated, and interactive-animated. The findings reveal that interactive objects dominate the game environment, accounting for an average of 60.25%, followed by animated objects at 29.39%, while interactive-animated objects comprise only 10.36%. These results suggest that the genre's classic design approach, which encourages active exploration, may also create control ambiguity due to the lack of explicit visual affordances, leading players to rely on trial-and-error exploration. This study is expected to contribute conceptually to game studies and serve as a reference for game developers in designing balanced interactions between player actions and consistent feedback.